Does a quantifiable difference exist in pre- and post-EFL regional and national identities? - Zwisler, Joshua James; Bejarano Vásquez, Hernando José (Rastros Rostros, 2023)
Studies regarding second language learning and national identity tend to, understandably, use small scale ethnographic studies of individuals who have participated in English as a Foreign Language education. Through Tajfel’s Social Identity Theory, this article asks whether a large-scale quantitative survey can demonstrate whether there exists a quantifiable difference in the local and national identities of regional Colombians who have had either no EFL education or different years of EFL exposure. A survey was distributed to 1000 people in the city of Ibagué with categories of 0,1,2, 3 and 4 years of EFL education, asking how strongly they associated as Colombians and Tolimenses (the state) and whether they feel that learning English has positively or negatively affected these identities. The results show statistically significant differences in the self-identification in both state and national identities with both identities being valued less after exposure to EFL. English as a foreign language education does have a quantifiable effect on Colombian national and Tolimense regional identities, and the value given to both identities is reduced over exposure to EFL but the change does not enter the range of negative association with the local identities at any point. Thus, the figures argue that identity change does take place, but the attitudes towards the identities are still relatively positive.